Effects of aeration and natural zeolite on ammonium removal during the treatment of sewage by mesocosm-scale constructed wetlands. Issue 14 (17th July 2016) - Araya, F.; Vera, I.; Sáez, K.; Vidal, G.
ABSTRACT: The objective was to evaluate the effects of intermittent artificial aeration cycles and natural zeolite as a support medium, in addition to the contribution of plants (Schoenoplectus californicus) on NH4 + –N removal during sewage treatment by Constructed Wetlands (CW). Two lines of Mesocosm Constructed Wetland (MCW) were installed: (a) gravel line (i.e. G-Line) and (b) zeolite line (i.e. Z-Line). Aeration increased the NH4 + –N removal efficiency by 20–45% in the G-Line. Natural zeolite increased the NH4 + –N removal efficiency by up to 60% in the Z-Line. Plants contributed 15–30% of the NH4 + –N removal efficiency and no difference between the G-Line and the Z-Line. Conversely, the NH4 + –N removal rate was shown to only increase with the use of natural zeolite. However, the MCW with natural zeolite, the NH4 + –N removal rate showed a direct relationship only with the NH4 + –N influent concentration. Additionally, relationship between the oxygen, energy and area regarding the NH4 + –N removal efficiency was established for 2.5–12.5 gO2 /(kWh-m 2 ) in the G-Line and 0.1–2.6 gO2 /(kWh-m 2 ) in the Z-Line. Finally, it was established that a combination of natural zeolite as a support medium and the aeration strategy in a single CW could regenerate the zeolite's adsorption sites and maintain a given NH4 + –N removal efficiency over time.